Attributes of carbapenemase encoding conjugative plasmid pNDM-SAL from an extensively drug-resistant Salmonella enterica Serovar Senftenberg - Sarkar, Anirban; Pazhani, Gururaja P.; Chowdhury, Goutam; Ghosh, Amit; Ramamurthy, Thandavarayan (Frontiers in Microbiology, 2015)
A carbapenem resistant Salmonella enterica serovar Senftenberg isolate BCH 2406 was isolated from a diarrheal child attending an outpatient unit of B.C. Roy Hospital in Kolkata, India. This isolate was positive for the blaNDM-1 in the PCR assay, which was confirmed by amplicon sequencing. Except for tetracycline, this isolate was resistant to all the tested antimicrobials. The blaNDM-1 was found to be located on a 146.13-kb mega plasmid pNDM-SAL, which could be conjugally transferred into Escherichia coli and other enteric pathogens such as Vibrio cholerae O1 Ogawa and Shigella flexneri 2a. However, the expression of β-lactam resistance is not the same in different bacteria. The whole genome sequence of pNDM-SAL was determined and compared with other pNDM plasmids available in public domain. This plasmid is an IncA/C incompatibility type composed of 155 predicted coding sequences and shares homology with plasmids of E. coli pNDM-1_Dok01, Klebsiella pNDM-KN, and Citrobacter pNDM-CIT. In pNDM-SAL, gene cluster containing blaNDM-1 was located between IS26 and IS4321 elements. Between the IS26 element and the blaNDM-1, a truncated ISAba125 insertion sequence was identified. Downstream of the blaNDM-1, other genes, such as bleMBL, trpF, tat, and an ISCR1 element with class 1 integron containing aac(6′)-Ib were detected. Another β-lactacamase gene, blaCMY -4 was found to be inserted in IS1 element within the type IV conjugative transfer loci of the plasmid. This gene cluster had blc and sugE downstream of the blaCMY -4. From our findings, it appears that the strain S. Senftenberg could have acquired the NDM plasmid from the other members of Enterobacteriaceae. Transfer of NDM plasmids poses a danger in the management of infectious diseases.